The impact of peer tutoring on librarians in training at the University of Ibadan, Nigeria (2013)
The enrichment of the national cultural heritage is directly linked to the level of protection given to literary and artistic works. The higher the level of protection, the greater the number of each country’s intellectual output. This calls for an effective copyright information resource management in every nation and organization to optimize access to relevant information on copyright in order to curb the rate of infringement. This paper seeks to address the copyright information resource management in Nigeria, and the way forward. Questionnaire instrument was used for data collection. The last two questions on the questionnaire were open-ended questions, designed to enable the respondents freely express their views and suggestions. The findings identified the benefits of copyright information resource management, both to the authors and the users; include the inhibition of infringement as it delivers quick access to copyright related information in a dynamic and effective way. This is due to the fact that many acts of infringement on copyright are as a result of ignorance on the part of users. The findings further highlighted that copyright information resource management facilitation is dependent on putting the right people in positions of authority, setting up committee in each institution to monitor and establish standards in order to ensure quality assurance in the system, and keeping tracks of publications of each university’s scholar